2006
DOI: 10.1080/15513810600788798
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Lipoid Pneumonia Superinfected With Acid-Fast Bacilli in Infants: A Report of Nine Cases

Abstract: Super-infection of an exogenous lipoid pneumonia by nontuberculous mycobacteria has been described in the literature. It produces a distinctive histologic picture with suppurative, noncaseating granulomas surrounding lipid vacuoles containing acid-fast bacilli. Mainly isolated cases have been found, but seldom in children. We describe a series of 9 children with similar histological findings. All our patients were under 1 year of age, malnourished, and with chronic respiratory symptoms. The diagnosis, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…All had presented with chronic respiratory symptoms and had underlying medical conditions, such as gastroesophageal reflux disease, mental retardation, and malnutrition. 7 Our patient did not fit the typical host at risk for RGM pneumonia; however, on further questioning of the parents, it became apparent that our patient had received several doses of mineral oil for constipation in the first 2 weeks of life, shortly before developing the first symptoms of respiratory distress. It is our opinion that superinfection with M. fortuitum occurred following colonization of the respiratory tract after lipid aspiration.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…All had presented with chronic respiratory symptoms and had underlying medical conditions, such as gastroesophageal reflux disease, mental retardation, and malnutrition. 7 Our patient did not fit the typical host at risk for RGM pneumonia; however, on further questioning of the parents, it became apparent that our patient had received several doses of mineral oil for constipation in the first 2 weeks of life, shortly before developing the first symptoms of respiratory distress. It is our opinion that superinfection with M. fortuitum occurred following colonization of the respiratory tract after lipid aspiration.…”
Section: Discussionmentioning
confidence: 67%
“…The diagnosis of lipoid pneumonia can easily be made by pathological examination of the lung tissue, but the presence of acid fast organisms may be missed, as bacilli can be lost along with the oil during the staining process. 7 Ridaura-Sanz et al 7 described a series of 9 infants from Mexico City with lipoid pneumonia and NTM infection. All 9 infants were diagnosed by lung biopsy or at autopsy and shared similar histology illustrating lipoid pneumonia and granulomatous abscesses containing acid fast bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…Though rare, subjects diagnosed with lipoid pneumonia are at risk for non-tuberculous mycobacteria, aspergillus and nocardia infections [11,31].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies identified non-tuberculous mycobacteria (NTM) co-infection cultured from blood or respiratory tract secretions. These included Mycobacterium fortuitum [10,40,41], M. fortuitum/chelonei [42], Mycobacterium smegmatis [31] and Mycobacterium abscessus complex [24]. Other infections described in the selected studies included Branhamella catarrhalis [35]; Pseudomonas, Acinetobacter, Klebsiella [20]; respiratory viruses including Adenovirus, Human Metapneumovirus, Human Bocavirus, Human Rhinovirus, Parainfluenza, Respiratory Syncytial virus A and B, Coronavirus and various bacteria and fungi [24]; Chlamydia on serology [39]; and Enterococcus, Escherichia coli, Klebsiella, coagulase positive Staphylococcus and Clostridium from peritoneal exudate [29] (Appendix C).…”
Section: Microbiologymentioning
confidence: 99%